O aplicativo Formatea no apoio à formação continuada em transtorno do espectro autista para professores do ensino médio no município de Bacabeira/MA - LUZ, Joelice Silva da (2024)
The objective of this dissertation was to develop the FORMATEA application with basic content on Autism Spectrum Disorder - ASD to support the continued training of teachers who work in teaching students with this neurodevelopmental disorder in the city of Bacabeira, Maranhão, Brazil. To this end, applied research of an exploratory nature was carried out using a qualitative approach. The platform chosen to create the prototype was Application Factory -FABAPP/São Paulo/SP. The participants were 9 teachers from the Monsenhor Alves Madureira Teaching Center, Bacabeira. For data collection, semi-structured interviews and systematic observations were used. The FORMATEA Application enabled teachers to interact through access to specific scientific content about ASD, proving to be an innovative and useful tool that meets the knowledge needs of students with this disorder and the educational specificities presented by them in the teaching-learning process. The FORMATEA application met emerging educational desires and needs, recognizing that technology can be used to support the training process of teachers to appropriate content that can support the teaching of students with ASD. Finally, we found that the FORMATEA application met teachers' needs for specific knowledge about ASD and, mainly, favoring knowledge that will guide inclusive pedagogical practices in the teaching process of students with ASD.